2020
DOI: 10.1111/jfbc.13199
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, antioxidant evaluation, and antidiabetic potential of Pinus gerardiana (Pine nuts) extracts

Abstract: Methanolic and ethyl acetate extracts of pine nuts were evaluated for in vitro antioxidant and inhibition of alpha‐amylase activities. Pine nut extracts were orally administered to alloxan monohydrate‐induced diabetes in mice at 250, 500, and 750 mg/kg. Both extracts showed a significant antioxidant and inhibition of alpha‐amylase activities. Animal studies showed a decline in fasting blood glucose, hyperlipidemia, and weight loss in diabetic mice. The administration of plant extracts decreased the blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…Besides Salmonella , neither Enterobacteriaceae, E. coli nor C. perfringens were found, but this must not lead to underestimating the antibacterial power of some ingredients of the pesto and sauces examined. Although a parameter for the selection of the examined foods was the absence of garlic, a food with demonstrated antibacterial activity [ 12 , 13 ], numerous scientific studies also demonstrated the antibacterial power of basil essential oil against these microorganisms [ 48 , 49 ] and of pine nuts [ 50 ], which are included in pesto; walnuts [ 51 ] and pore mushroom [ 52 ] also showed antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Besides Salmonella , neither Enterobacteriaceae, E. coli nor C. perfringens were found, but this must not lead to underestimating the antibacterial power of some ingredients of the pesto and sauces examined. Although a parameter for the selection of the examined foods was the absence of garlic, a food with demonstrated antibacterial activity [ 12 , 13 ], numerous scientific studies also demonstrated the antibacterial power of basil essential oil against these microorganisms [ 48 , 49 ] and of pine nuts [ 50 ], which are included in pesto; walnuts [ 51 ] and pore mushroom [ 52 ] also showed antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance was measured at 415 nm using UV-visible spectrophotometer. Flavonoid contents were measured as quercetin equivalent (QE) and expressed as (QE mg/g of Cyperus iria aqueous-ethanol extract) (Zulfqar et al 2020).…”
Section: Total Flavonoid Contentsmentioning
confidence: 99%
“…Blood samples were taken on 20th day of pregnancy or the corresponding day in nonpregnant rats by cardiac puncture for the evaluation of complete blood count (CBC), liver function biomarkers including bilirubin, total protein, aspartate aminotransferase (ALT), alanine transaminase (AST), and renal function tests such as urea and creatinine. Lipid profile including low density lipoprotein (LDL), cholesterol, triglycerides, and high-density lipoprotein (HDL) were also determined by previous methods (Zulfqar et al, 2020).…”
Section: Hematological and Biochemical Analysismentioning
confidence: 99%